Reactivity‐Tuning in Frustrated Lewis Pairs: Nucleophilicity and Lewis Basicity of Sterically Hindered Phosphines. Issue 31 (4th May 2017) - Follet, Elsa; Mayer, Peter; Stephenson, David S.; Ofial, Armin R.; Berionni, Guillaume
Abstract: The nucleophilicity and Lewis basicity of sterically hindered phosphines, widely used in catalysis and in frustrated Lewis pair (FLP) chemistry, have been quantified by determining the rates and equilibrium constants of their associations with reference systems (benzhydrylium and tritylium ions) of calibrated electrophilicities and Lewis acidities. These structure–reactivity investigations allow a rationalization of the Lewis acid–base interactions all along the way from covalent Lewis adducts to FLPs. Comparisons of the association of phosphines of increasing sizes (Ph3 P, ( o ‐tolyl)3 P, and t Bu3 P) with the triarylborane B(C6 F5 )3 and with the isoelectronic tritylium ions Ar3 C + provide detailed insights for the future fine‐tuning of the reactivities of FLPs. As a proof of concept, tritylium‐ion‐derived FLPs were shown to react with alkynes, as reported for the FLPs derived from the benchmark triarylborane B(C6 F5 )3 . Abstract : The Lewis basicities and nucleophilicities of sterically hindered phosphines were determined and used for investigating the structure of carbenium‐ion‐derived frustrated Lewis pairs and their reactivities towards terminal alkynes (see figure).